2010
DOI: 10.1002/rcs.341
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming extreme obesity with robotic surgery

Abstract: Since obesity is a significant risk factor for endometrial cancer and the prevalence of obesity is increasing, developing surgical techniques to appropriately manage these patients is important. Minimally invasive surgery, specifically with robotic assistance, has increased the possibilities of performing minimally invasive surgery in morbidly obese women. It allows navigation around anatomical barriers and decreases the fatigue experienced by the surgeons. With the increasing obesity of our population and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Robot assisted total laparoscopic hysterectomy (TRH) is an increasingly available alternative that may confer an advantage in obese and other complex patients by lowering the need for conversion. Successful TRH for endometrial cancer in the setting of extreme obesity (BMI 98) has been described in the literature with patient discharge on postoperative day one [11]. Moreover, several retrospective studies have demonstrated equivalent safety and short-term clinical outcomes between TRH and alternate methods [1215].…”
Section: Introductionmentioning
confidence: 99%
“…Robot assisted total laparoscopic hysterectomy (TRH) is an increasingly available alternative that may confer an advantage in obese and other complex patients by lowering the need for conversion. Successful TRH for endometrial cancer in the setting of extreme obesity (BMI 98) has been described in the literature with patient discharge on postoperative day one [11]. Moreover, several retrospective studies have demonstrated equivalent safety and short-term clinical outcomes between TRH and alternate methods [1215].…”
Section: Introductionmentioning
confidence: 99%
“…20 Although conversion to open laparotomy has been observed with increasing BMI >30 kg/m 2 , 21 a robotic-assisted hysterectomy has been reported in a patient with a BMI of 98% (height of 160 cm and weight of 252 kg). 22 …”
Section: Discussionmentioning
confidence: 99%
“…There are examples of extremely obese patients treated with the use of robotics, as reported in one case of gynecological cancer operated by robot-assisted surgery in a patient with a BMI of 98. This example illustrates the easiness that the robotic system gives in the operation of the obese patients compared to traditional laparoscopy 8 .…”
Section: Introductionmentioning
confidence: 94%